Management of recurrent vulvovaginal candidosis: Narrative review of the literature and European expert panel opinion - Donders, Gilbert; Sziller, István Oszkár; Paavonen, Jorma; Hay, Phillip; de Seta, Francesco; Bohbot, Jean Marc; Kotarski, Jan; Vives, Jordi Antoni; Szabo, Bela; Cepuliené, Ramona; Mendling, Werner (Frontiers in Cellular and Infection Microbiology, 2022)
Recurrent vulvovaginal candidosis (RVVC) is a chronic, difficult to treat vaginal infection, caused by Candida species, which affects women of all ages and ethnic and social background. A long-term prophylactic maintenance regimen with antifungals is often necessary. In most clinical practice guidelines, oral fluconazole is recommended as the first-line treatment. Although clinical resistance to antifungal agents remains rare, overexposure to azoles may increase the development of fluconazole-resistant C. albicans strains. In addition, non-albicans Candida species are frequently dose-dependent susceptible or resistant to fluconazole and other azoles, and their prevalence is rising. Available therapeutic options to treat such fluconazole-resistant C. albicans and low susceptibility non-albicans strains are limited. Ten experts from different European countries discussed problematic issues of current RVVC diagnosis and treatment in two audiotaped online sessions and two electronic follow-up rounds. A total of 340 statements were transcribed, summarized, and compared with published evidence. The profile of patients with RVVC, their care pathways, current therapeutic needs, and potential value of novel drugs were addressed. Correct diagnosis, right treatment choice, and patient education to obtain adherence to therapy regimens are crucial for successful RVVC treatment. As therapeutic options are limited, innovative strategies are required. Well- tolerated and effective new drugs with an optimized mechanism of action are desirable and are discussed. Research into the impact of RVVC and treatments on health-related quality of life and sex life is also needed.